BUMDes management patterns in improving the village economy at Ngawun Bersatu BUMDes, Tuban Regency - Yusuf Hariyoko (Publisia: Jurnal Ilmu Administrasi Publik, 2023)
BUMDes as a component of village development serves in creating and growing the village economic sector. BUMDes Ngawun Bersatu owned by Ngawun Village has a rest area business sector with the name tabeplast forest area (TFA) because of its location in the inter-provincial road access. In the managerial BUMDes Ngawun Bersatu has gone well by appointing parties outside the Ngawun Village Government as the directors / managers of BUMDes. The role of the community is still minimal, esrta on bumdes innovation is still not able to develop the potential of other villages in the field of agriculture. BUMDes Ngawun Bersatu has provided employment for youth in managing tourist areas, but it can still be developed again by providing opportunities also to the wider community to provide its products in the tourist area. The development of MSMEs through BUMDes is still not developed, whereas with BUMDes is expected to encourage MSMEs. The development of village potential becomes a big task that bumdes must think about to create a positive economic development for the community that until now has not been optimal development.